The invasion threat of the emerging alien cactus Cylindropuntia pallida (Rosa), F.M. Knuth in South Africa and the potential for control using herbicides - Thabiso Michael Mokotjomela; Takalani Nelufule; Zimbini Scott; Loyd Rodney Vukeya; Travor Xivuri; King Matsokane; Nobuhle Mweli; Felicia Lerato Magqabi; Thulisile Jaca (Environmental Monitoring and Assessment, 2024)
The emerging alien cactus Cylindropuntia pallida (Rose) F.M. Knuth originates from northern Mexico and introduced into South Africa in 1940s as an ornamental plant. Multiple populations of C. pallida have been detected in various areas of South Africa. C. pallida has effective propagule dispersal and rapid recruitment making it a likely key future invader, and thus, is a target for eradication in South Africa. To eradicate C. pallida populations, a foliar spray (i.e. using a 2% concentration of herbicide with fluroxypyr and triclopyr) has been applied to plants in nine populations, with population sizes ranging between 535 and 2701 plants and populations covering areas of 100 –1000 ha. The aims of the study were to investigate the efficacy of the foliar spray method used to eradicate C. pallida ; to investigate the impacts of C. pallida invasions on native vegetation integrity; to apply species distribution models (SDMs) to identify suitable climates for C. pallida in South Africa; and to document the biomes vulnerable to the negative impact of C. pallida in South Africa. Results show that foliar spray killed many C. pallida plants (mean percentage of dead plants ± SE, 83.3 ± 6.4; n = 9; range, 70–96%), with adult plants taking about 2 months to die completely. The efficacy of the herbicide was not affected by plant size or the concentration of the herbicide used. The invaded site had significantly greater vegetation cover which persisted across winter compared to the uninvaded site, but the latter site’s vegetation cover significantly dropped in winter. Also, the invaded site had lower plant species diversity than the uninvaded site and was dominated by species in the Poaceae and Asteraceae plant families. Additionally, a normalised difference vegetation index (NDVI) analysis shows that the uninvaded site has higher vegetation cover and health than the invaded site wherein a notable decline in vegetation health was observed between 2019 and 2022. A large area (> 15 million hectares) was predicted to be suitable for invasion by C. pallida in provinces with arid and warm temperate climates - the fynbos and grassland biomes are the most vulnerable. Because of the observed negative impacts, high environmental compatibility, and high cost of clearing large infestations, we advocate for considering the biocontrol method for effectively managing C. pallida invasion in South Africa.